Life-cycle environmental benefits of using bioethanol as a gasoline additive - Tan, Raymond R. (Philippine Engineering Journal)
Ethanol can be blended with gasoline as a fuel extender, an oxygenating agent, an octane enhancer. Blends containing up to 10 percent ethanol by volume (E10) can be used in unmodified spark ignition engines without significant changes in vehicle performance, while yielding reductions in over-all tailpipe emissions. Enzyme-based processing technology is expected to allow ethanol to be produced commercially from cellulosic biomass such as municipal and agricultural aste as early as 2005. Ethyl alcohol produced in this manner is called bioethanol; this production technology promises to be an effective open-loop recycling ("waste to energy") pathway which simultaneously gives significant benefits of reduced fossil fuel consumption and air emissions. This paper presents results of simulations using a modified version of the GREET 1.5 a fuel cycle model to estimate the relative benefits of using E10 instead of conventional gasoline. In addition to obvious savings in petroleum usage, reductions in life cycle hydrocarbon, carbon monoxide, sulfur dioxide and carbon dioxide emissions are predicted by the model. Cumulative emissions of particulates and nitrogen oxides, on the other hand, are expected to increase.